2016
DOI: 10.1002/bies.201600018
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory effects of melatonin in multiple sclerosis

Abstract: Melatonin is a hormone with complex roles in the pathogenesis of autoimmune disorders. Over the years, it has become clear that melatonin may exacerbate some autoimmune conditions, whereas it alleviates others such as multiple sclerosis. Multiple sclerosis is an autoimmune disorder characterized by a dysregulated immune response directed against the central nervous system. Indeed, the balance between pathogenic CD4(+) T cells secreting IFN-γ (TH 1) or IL-17 (TH 17); and FoxP3(+) regulatory T cells and IL-10(+)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 130 publications
0
31
0
1
Order By: Relevance
“…These include immunomodulatory and beneficial effects in a devastating disease, multiple sclerosis (MS), as was nicely discussed by Farez et al [3]. As much we agree with the majority of opinions in that paper, we are obliged to correct the cited theory on melatonin acting as a ligand for RORα or RORγ [3]. …”
Section: Sirmentioning
confidence: 80%
See 2 more Smart Citations
“…These include immunomodulatory and beneficial effects in a devastating disease, multiple sclerosis (MS), as was nicely discussed by Farez et al [3]. As much we agree with the majority of opinions in that paper, we are obliged to correct the cited theory on melatonin acting as a ligand for RORα or RORγ [3]. …”
Section: Sirmentioning
confidence: 80%
“…Melatonin and its various metabolites exhibit many diverse pleiotropic activities triggered by receptor dependent and independent signaling pathways [2]. These include immunomodulatory and beneficial effects in a devastating disease, multiple sclerosis (MS), as was nicely discussed by Farez et al [3]. As much we agree with the majority of opinions in that paper, we are obliged to correct the cited theory on melatonin acting as a ligand for RORα or RORγ [3].…”
Section: Sirmentioning
confidence: 97%
See 1 more Smart Citation
“…MT 1 has a somewhat higher affinity to melatonin (pK i ≈ 9.48‐10.85) than MT 2 (pK i ≈9.60‐9.95), according to determinations summarized elsewhere . Although it has been shown that melatonin does not directly activate RORα, melatonin seems to indirectly affect transcriptional activities that are downstream of RORα . There is convincing evidence that macrophages express melatonin membrane receptors and also the possibly melatonin‐regulated RORα .…”
Section: Melatonergic Systems In Macrophagesmentioning
confidence: 92%
“…The pineal gland hormone melatonin ( N ‐acetyl‐5‐methoxytryptamine) has been shown to play an important role in many physiological processes, including controlling sleep‐wake rhythms, regulation of circadian cycle, cardiovascular function, immune defense, renal function, detoxification, as well as bone metabolism . In addition to these functions, numerous studies also demonstrated that melatonin can serve as one of the most powerful endogenous antioxidant agents by direct and indirect ways .…”
Section: Introductionmentioning
confidence: 99%